The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00737-007-0186-8
|View full text |Cite
|
Sign up to set email alerts
|

Stable serum levels of relaxin throughout the menstrual cycle: a preliminary comparison of women with premenstrual dysphoria and controls

Abstract: Serum levels of relaxin in 25 women with premenstrual dysphoria and 25 age-matched controls were determined at three time points during the menstrual cycle. At the same time, levels of estradiol, progesterone, 17-beta-OH-progesterone, free testosterone, total testosterone, sex hormone binding hormone, androstenedione, dehydroepiandrosterone sulphate, and 3-alpha-androstanediol glucuronide were determined. Detectable levels of relaxin were found in all women in both the follicular and luteal phase as well as ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
12
1
Order By: Relevance
“…The SRCs among our athletes were also lower than those reported by Stewart13 among women with nonconceptive cycles (30–150 pg/mL). Additionally, these SRCs were lower than those reported among older parous women by Binder et al (260–620 pg/mL, Santa Cruz Biotechnology Inc. assay),23 by Pehrrson et al (144–4500 pg/mL, Immunodiagnostix assay),22 and by Wreje et al (20–255 ng/L, Genentech reagents) 34. Just as all these studies reported 1 to several participants with unexpectedly high SRCs, our study also revealed outliers.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…The SRCs among our athletes were also lower than those reported by Stewart13 among women with nonconceptive cycles (30–150 pg/mL). Additionally, these SRCs were lower than those reported among older parous women by Binder et al (260–620 pg/mL, Santa Cruz Biotechnology Inc. assay),23 by Pehrrson et al (144–4500 pg/mL, Immunodiagnostix assay),22 and by Wreje et al (20–255 ng/L, Genentech reagents) 34. Just as all these studies reported 1 to several participants with unexpectedly high SRCs, our study also revealed outliers.…”
Section: Discussioncontrasting
confidence: 52%
“…However, the majority of previously used assays do not report their level of specificity or cross-reactivity profiles. Only a couple have reported having no cross reactivity with insulin,22,23 or IGF-1 23. Lastly, this difference could also reflect a sustained increase in SRC among primi- or multiparous women, which makes their SRCs significantly higher than those of nulligravidae women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…105 Differences in levels of relaxin—a reproduction-related peptide (e.g., in pregnancy-associated changes in the cervix and pubic symphysis)—also were reported, although levels were not linked to symptom expression. 106 …”
Section: Etiologymentioning
confidence: 99%
“…Because relaxin rises and peaks during a relatively short window (6-10 days) after ovulation based on other hormonal events, [217][218][219][220] we do not know if the high proportion of undetectable levels within a single sample (as high as 64%-80%) [221][222][223][224] is due to timing or suggests that only a subset of females are exposed to appreciable relaxin levels due to mediating factors. 219,221,225 5. Because cyclic hormone concentrations affect soft tissues and knee-joint function, studies comparing females with males should be made during the early follicular phase in females, when hormone levels are at their nadirs (preferably 3-7 days postmenses).…”
Section: Good Evidence Demonstrates That Some (But Not All)mentioning
confidence: 99%